(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: As Millions of people are receiving COVID-19 vaccine around the world, a number of side effects are being reported. Menstrual cycle disturbance is also a side effect reported by hundreds of women on social media. The objective of this study was to assess the association of menstrual abnormalities with COVID-19 vaccination. Subjects and methods: This descriptive cross sectional study was conducted in Obstetrics and Gynecology OPD of Mufti Mehmood Hospital D.I. Khan from March 2021 to June 2021. The health care workers who received Sinopharm COVID-19 vaccine and consented were included. Data was collected about change in menstrual cycle pattern after COVID-19 vaccination. Results: A total of 80 subjects were included in the study with mean age of 32.6 +7.89 years. There were 36 (45.0%) doctors, 33 nurses (41.25%), 6 (7.5%) paramedics and 5 (6.25%) medical students. According to their marital status, 51 (63.75%) were married and 29 (36.25%) were unmarried. Out of 80 subjects, 16 (20%) reported disturbance in menstrual cycle pattern, 13 (81.2%) after first dose and 3 (18.75%) after both first and second dose. Among these 9 (56.25%) reported heavy menstrual bleeding, 4 (25%) had prolonged bleeding days while 3 (18.75%) had irregular bleeding pattern. Conclusion: Menstrual cycle disturbance is a reported side effect of COVID-19 vaccination. It is more commonly reported after first dose and heavy menstrual bleedings is the most common pattern followed by prolonged/irregular bleeding.